The effect of online learning on student involvement and achievement in Permatang Pauh Campus, UiTM Cawangan Pulau Pinang (UiTMCPP) / Atiq Najwa Marzuki ... [et al.] - Marzuki, Atiq Najwa; Kamil Azmi, Salsabila; Khairulnaim, Siti Zulaikha; Mazeni, Noor Azizah (Unit Penerbitan JSKM, 2025)
This study investigates the effects of online learning on student engagement and academic achievement at the Permatang Pauh Campus of Universiti Teknologi MARA Cawangan Pulau Pinang (UiTMCPP). As the institution transitioned from traditional face-to-face learning to online education during the COVID-19 pandemic, students faced both opportunities and challenges. The study employed a questionnaire-based survey targeting 82 students from Culinary Arts Management, Mechanical Engineering, and Electrical Engineering programs. A sample of 34 students was selected using simple random sampling, and data were analyzed using descriptive and inferential statistics, including ANOVA and chi-square tests. The findings revealed that while online learning provided flexibility and accessibility, it also led to varying levels of student engagement and academic performance. Some students reported increased participation, while others struggled with motivation and concentration. The ANOVA results indicated significant differences in GPA among the three academic programs, suggesting that the effectiveness of online learning varied by field of study. The study highlights the need for enhanced online learning strategies, including interactive course designs and real-time feedback mechanisms, to improve student engagement and academic outcomes. Future research should explore long-term trends in online education to further refine instructional practices.